(untitled) (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: Stigma is a sign of disgrace or discredit that sets a person apart from others. Stigma has detrimental effect on stigmatized persons’ life which may even hamper or delay the help seeking behavior, which ultimately increases the duration of untreated mental illness. Material And Method: A cross sectional survey was conducted among 90 psychiatry outpatients attending Manipal Teaching Hospital, Pokhara, Nepal. Discrimination and disclosure sub-scale of the Stigma scale and ISMI- 10 was administered to measure the extent of stigma. Help seeking delay was assessed using pre- structured questionnaire. Prediction of help seeking delay due to stigma was identified using logistic regression. Results: Low mean value on the subscales of the Stigma scale indicated low public stigma in the participants. 34% of the study population exhibited moderate to high self stigma. The full model for initial help seeking delay using logistic regression explained 21.8% (Cox and Snell R square) and 31.5% (Nagelkerke R square) of the variance in initial help seeking delay while the model for the recent help seeking delay explained 13.6% (Cox and Snell R square) and 20.8 % (Nagelkerke R square) of the variance in recent help seeking delay. The strongest predictor of both initial and recent help seeking delay was discrimination subscale (OR= 1.11; 95% CI= 1.033- 1.195). Conclusion: Discrimination experienced due to stigmatization leads to delay in help seeking behavior. Public stigma experienced by stigmatized individual acts as a stronger predictor for help seeking delay than self stigma.